Effects of Naked-Neck and Frizzle Genes on Growth Performance and Carcass Characteristics Of Crossbred Cockerels (Journal of Science and Technology, 2016)
An experiment was carried out to evaluate the performance of crossbred naked-neck and frizzle cockerel genotypes namely: (i) Na/naF/f, (ii) Na/naf/f (iii) na/naF/f and (iv) na/naf/f. These crossbred second generation cockerels were generated from a reciprocal crossing between crossbred heterozygous naked-neck (50% indigenous naked-neck and 50% Lohman Brown) and frizzle (50% indigenous frizzle and 50% Lohman Brown) stocks. One hundred and twenty (120), eight-week old crossbred cockerels (thirty each of the four genotypic groups) were randomly assigned to nine deep litter pens in a Completely Randomized Design for six weeks and their growth and carcass characteristics evaluated. The birds were provided with grower mash ad lib throughout the experimental period. At the end of the trial, 3 cockerels from each of the four genotypic groups were randomly selected and slaughtered and their carcass parameters determined. The results indicated that there was no significant genotype effect on both initial and final body weights. There were also no genotype effects on weight gain, feed intake, mortality and feed conversion ratio. With respect to carcass yield characteristics, the double heterozygous cockerels had significantly (P